ERGONOMIC RISK ASSESSMENT OF GADUNG PEELERS USING NORDIC BODY MAP (NBM) AND OVAKO WORK POSTURE ANALYSIS (OWAS) METHODS - Rahmania, Nima Eka Nur; Kuncoro, Achmat; Irianingtyas, Riza; Nuwa, Geovania Nage (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The activity of peeling gadung as a raw material for making gadung chips is done manually and repeatedly with an unnatural working posture and can cause musculoskeletal disorders (MSDs). Preventive measures need to be taken by carrying out ergonomic risk assessments. Objectives: The research aimed to analyze the level of ergonomic risk in MSDs using the Nordic Body Map (NBM) and Ovako Work Posture Analysis (OWAS) methods. Methods: The research method used was an analytical method with a cross-sectional research design. This research was conducted in the home industry gadung chips, Kediri in August 2024. The sampling technique was purposive sampling with a total sample of 10 gadung peeler workers. The variables in this study were the severity of muscle complaints and work posture (back, arm, leg, and load movements) as the risk level for MSDs. The type of data collection technique used was a field study by filling out the NBM questionnaire to determine the severity of MSDs. Working posture (back, arm, leg, and load movements) was also observed using the OWAS method by filling in a form. The results of the analysis will provide results as a reference for taking appropriate action to overcome ergonomic risks. Results: Based on data analysis using the NBM showed the percentage of MSDs, that are right shoulder, right wrist, and right hand had the highest proportion of scores for complaints of pain that always occurred (100%). The left wrist and shoulder area (96%), stiffness in the lower neck (92%), pain in the back (91%), pain in the waist (90%), and also pain in the right and left knee areas for lower limbs. The results of the ergonomic risk level analysis using the OWAS method showed that the working posture is included in the moderate risk category (score 2). Conclusion: Corrective action is needed to prevent musculoskeletal disorders such as improving work posture, doing stretching exercises before and after work and designing ergonomic work chairs.